Co-administration of saffron and chamomile: to determine the efficacy as an adjuvant therapy for mild to moderate depression in human subjects. A pilot randomized clinical trial - Saara Ahmad,; Khan, Asra; Rafiq, Hamna; Tikmani, Prashant; Mesiya, Hanif; Amin, Faiq (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine the combined effects of chamomile and saffron herbs as an adjuvant therapy in patients with metabolic alterations associated with mild to moderate depression. Method: The prospective, randomised, blinded, end-point pilot study was conducted at the Aga Khan University, Karachi, from August to October 2020, and comprised patients with mild to moderate depression with or without diabetes, hypertension and dyslipidaemia. The subjects were randomised into intervention group A, which was given herbal tea sachets containing saffron 1mg and chamomile 20mg for twice a day oral use for a month along with medications, and control group B, which was advised to continue their routine medications. Data was collected at baseline and post-intervention using Patient Health Questionnaire-9 for assessing depression severity, and blood samples for cholesterol estimations. Data was analysed using SPSS 20. Results: Of the 50 subjects, 25(50%) were in each of the two groups. Cholesterol, high-density lipoprotein, low-density lipoprotein and depression values were significantly better in group A than in group B (p<0.05). Conclusion: Potential benefits of combined doses of chamomile and saffron were found in depressive patients by improving metabolic alterations. Key Words: Chamomile, Saffron, Depression, Hyperlipidaemia.